A Comparative Study of Anopheles Gambiae Male Mosquito’s Response to Frequency Modulated [FM] and Pulse Modulated [PM] Waves at Different Acoustic Frequencies and Distances - Maweu Maweu; Muia L. M; Deng A. L (Institut Teknologi Bandung, 2009)
The efficiency of an electronic device meant to disrupt acoustic communication between male and female Anopheles gambiae mosquitoes was tested by recording approaches of the males towards the device as a function of distance and frequency. Different bioassays were conducted with broadcasts from the device and taped mimics of the female species wing beats at different distances and frequencies. A large number of the males, 85% remained near the broadcast speaker for a significantly longer period when the broadcast sounds of the device were at 380 Hz than at any other frequency range. The taped mimic sounds of the female mosquitoes in flight elicited a maximum response rate of 75 %. A test involving a choice between the device and taped sound mimics by male mosquitoes revealed that a high number (75 %) of them flew towards the device while 10% were attracted by the taped sounds whereas 15 % were undecided and made oscillatory motion between the two sources. Additional bioassays conducted to examine the effect of the device on non-flying males showed that almost 75 % were disturbed and approached the speaker within a distance of 0.5 m, which confirmed a radiative near-field communication for these insects.